Criminology explains school bullying - Brooks, Robert Andrew (Criminology explains, 2020)
The nature, scope, and response to school bullying -- Deterrence, rational choice, and victimization theories -- Micro-level theories -- Social structure theories -- Social process theories -- Critical criminology and restorative justice -- Integrationist perspectives